Phytodiversity of Ethnomedicinal Plants in Sacred Groves and its Traditional Uses in Kabirdham District of Chhattisgarh - Rahangdale, C. P.; Patley, R. K.; Yadav, K. C. (Indian Forester, 2014)
The paper describes distribution and local/traditional uses of the 100 ethno-medicinal plants belonging to 85 genera and 47 families present in Kabiradham district of Chhattisgarh state. Out of these, 58 species are trees, 23 herbs, 14 shrubs, 3 climbers and 2 palms. These identified plants need protection from the biotic pressure. Various plant parts, such as bark (31), leaves and fruit (30 each), root (25), seed (18), whole plant (12), gum (10), flowers and stem (5 each), sap, wood and rhizome (4 each), bulb, oil and latex (3 each), pod (2) and bud, tadi, thorn and resin (1 each) were used for treatment of different ailments.